Rapid metastasis of mediastinal solitary fibrous tumor: Report a case. Issue 51 (December 2017) - Xiang, Yingming; Tu, Shaosong; Zhang, Fangbiao
Abstract: Rationale: Mediastinal solitary fibrous tumors (SFTs) are rare mesenchymal neoplasms. Complete resection is considered as the effective treatment and the prognosis is quite good. Rapid metastasis after surgery is extremely rare. Patient concerns: In this case report we describe a 42-year-old man who present with a mediastinal malignant SFTs. Enhanced computed tomography of chest revealed a 4.5 × 4.0-cm mass in the anterior mediastinum. Diagnoses: The tumor is composed of massive proliferation of atypical spindle cells. Immunohistochemical staining for cluster of differentiation (CD) 34, CD99, and vimentin were strongly positive. Interventions: Due to the possibility that the tumor was malignant, a standard median sternotomy was performed under general anesthesia. The mediastinal tumor and the affected part of the pericardium and right upper lobe of the lung were completely resected. Outcomes: The patient underwent surgery and recovered uneventfully. After 2 months follow-up postoperation, there was recurrence in the chest wall and right middle lung. The patient refused any treatment and was dead after 2 months. Lessons: The present cases indicate that mediastinal SFTs should always be kept in mind for rapid metastasis. Once found, surgical intervention should be performed promptly. Due to the rapid metastasis, radiotherapy, and chemotherapy may be needed after surgery and long-term follow-up is required to monitor the metastasis of this type of tumor.